The role of Instagram influencers as a source of fashion information - Tomovska Elena (Tekstilna industrija, 2020)
Social media has become a powerful communicating tool for the fashion industry, providing an instant, democratic, user-generated dissemination of fashion trends, particularly with the younger generations. Image-centred social media, such as Instagram are particularly well adopted for fashion communication. This research aims to investigate the role of Instagram on the dissemination of fashion trends amongst Generation Z. The research used an electronic questionnaire distributed to 120 participants, aged 16 to 23 years. A commercially available tool for measuring the reach of global and local fashion influencers was used to comprise a list of influencers used in the research. Cluster analysis was used to identify Instagram influencers impacting fashion and the use of Instagram as a fashion information channel.